Cultivation of Inonotus hispidus in Stirred Tank and Wave Bag Bioreactors to Produce the Natural Colorant Hispidin - Pia Bergmann; Meike Takenberg; Christina Frank; Marlen Zschätzsch; Anett Werner; Ralf G. Berger; Franziska Ersoy (Fermentation, 2022)
Hispidin (6-(3,4-dihydroxystyrl)-4-hydroxy-2-pyrone) production in submerged cultured mycelia of the basidiomycete Inonotus hispidus was doubled in shake flasks through irradiation with white light. The daily addition of 1 mM hydrogen peroxide as a chemical stressor and a repeated supplementation of the shake flask cultures with 2 mM caffeic acid, a biogenetic precursor, further increased the hispidin synthesis. These cultivation conditions were combined and applied to parallel fermentation trials on the 4 L scale using a classical stirred tank bioreactor and a wave bag bioreactor. No significant differences in biomass yield and colorant production were observed. The hispidin concentration in both bioreactors reached 5.5 g·L−1, the highest ever published. Textile dyeing with hispidin was successful, but impeded by its limited light stability in comparison to industrial dyes. However, following the idea of sustainability and the flawless toxicity profile, applications in natural cosmetics, other daily implements, or even therapeutics appear promising.